(untitled) (International Journal of Engineering and Computer Science, 2014)
In recent years, vortex generators such as fins, notches, wings etc. have been successfully used for heat transfer enhancement of the modern thermal systems like dryers, electronic equipments etc. The aim of present study is to investigate Heat transfer coefficient in rectangular plates using various shapes such as spherical wings, tubular wings , bare plate using different material such as Copper, Brass and M.S plates and comparing the results using CFD Analysis and developing Mathematical modeling of the results. Therefore, a forced convection experimental setup is to be built to study the various parameters such as heat transfer coefficient, Reynolds number and Nusselt number.